HOLY WATER SOURCE: PHETCHABURI RIVER - (Kasem Rodjakthuk), Phrakru Kasemwatcharadit; Thamasaro (Saeou), Phra Saroj (Journal of MCU Phetchaburi Review, 2021)
Tha Chaisiri Temple Pier It is a place to draw water to be used in the royal coronation ceremony of the King Rama VI, Rama IX and the royal coronation ceremony Then uses water from the Petchaburi River at Tha Chaisiri Temple Pier Reasons for the Petchaburi River at Tha Chaisiri Temple Pier Used as a sacred water source of the province. This is because it is the place where the Thai monarchs use it for the three reigns of the Thai King, which is during the reign of His Majesty the King. King Rama IV, King Rama V, King Rama V and King Rama VI, King Rama VI. And senior government officials As well as being used as drinking water, used for ambassadors, The four sacred ponds are located in Tambon Sa Kaeo. Suphanburi Province His Majesty King Chulalongkorn used to come and see the holy pond at this sub-district. Therefore, the village's name was changed to "Ban Tha Sadet," a sacred pool initially found only four banks, namely Sa Kaeo, Sa Kha, Sa Yomanasaket, and later found two more Amrit and Sa Amrit. Maratha Phisek pond ceremony according to Brahmanism The Fine Arts Department has registered the establishment of a sacred pond. It is an archaeological site, but the water used in the coronation ceremony can be found as evidence of the government ordering the governor of Phetchaburi Diamond water was used in the coronation ceremony since King Mongkut. His Majesty King Chulalongkorn Since then, until the present reign, they used diamond water and performed a ritual to draw water at Tha Saisiri Temple.